Rocio virus: An updated view on an elusive flavivirus - Saivish, Marielena Vogel; da Costa, Vivaldo Gomes [UNESP]; Menezes, Gabriela de Lima; da Silva, Roosevelt Alves; da Silva, Gislaine Celestino Dutra; Moreli, Marcos Lázaro; Sacchetto, Livia; Pacca, Carolina Colombelli [UNESP]; Vasilakis, Nikos; Nogueira, Maurício Lacerda (MDPI, 2021)
Rocio virus (ROCV) is a mosquito-borne flavivirus and human pathogen. The virus is indigenous to Brazil and was first detected in 1975 in the Sao Paulo State, and over a period of two years was responsible for several epidemics of meningoencephalitis in coastal communities leading to over 100 deaths. The vast majority of ROCV infections are believed to be subclinical and clinical manifestations can range from uncomplicated fever to fatal meningoencephalitis. Birds are the natural reservoir and amplification hosts and ROCV is maintained in nature in a mosquito-bird-mosquito transmission cycle, primarily involving Psorophora ferox mosquitoes. While ROCV has remained mostly undetected since 1976, in 2011 it re-emerged in Goiás State causing a limited outbreak. Control of ROCV outbreaks depends on sustainable vector control measures and public education. To date there is no specific treatment or licensed vaccine available. Here we provide an overview of the ecology, transmission cycles, epidemiology, pathogenesis, and treatment options, aiming to improve our ability to understand, predict, and ideally avert further ROCV emergence.
Keywords: Clinical manifestations; Epidemiology; Pathogenesis; Rocio virus; Transmission cycles